The Centrality of Schools in the Lifecourse: The Case for Focusing on School-Related Influences in Developmental Theory and Research. Issue 7 (2nd July 2016) - Payne, Allison Ann; Welch, Kelly
ABSTRACT: While the strength of the lifecourse/developmental (LCD) perspective in the examination of antisocial behavior has been clearly demonstrated, this work has given little attention to schools and education as salient influences. By contrast, there is much research using other theoretical frameworks to examine school-related risk factors of deviance. Given what we know about the importance of schooling and education on individual development and subsequent implications for behavior, we contend that academic influences should be more prevalent in LCD theories of deviance and that research using an LCD theoretical perspective should embrace non-LCD work examining school-related risk factors of antisocial behavior.